ANALISIS TINGKAT KEPUASAN NASABAH NON MUSLIM TERHADAP KUALITAS PELAYANAN PADA BANK SYARIAH DI KOTA MEDAN - Miftah Farid (Ekonomi dan Keuangan, 2013)
Research aims to analyze the level of non-muslim customer satisfaction with quality of services in the field of Islamic banks in the city and analyze the service attributes that should be corrected by the employee in improving services performance.Data obtained from 100 non-muslim customers. Testing using 6 indicators are tangible, reliability, responsiveness, assurance, emphaty and customer satisfaction. Analysis methode used is descriptive analysis, Customer satisfaction index (CSI), Importance Performance Analysist (IPA). Validity and reability to the table is the value of or 0,5%.The test results prove that the costumer satisfaction related to the quality of services provided to the customers of Islamic banks, roommates is based on analysis of customer satisfaction levels of non-muslim towards service quality in islamic banks are satisfied that the presentation of 68,9%, roommates means that the non-muslim customers are satisfied Islamic banks to service the city field. While to increase of customers satisfaction then the Islamic banks should improve the performance attributes of clarity employees convey information, delivering survices to set an appointment that has been agreed upon, facility space, office equipment modern, good service, service satisfaction, building a good relationship to cutomers.Keywords : tangibles, reliability, responsiveness, assurance, emphaty, customers satisfaction